The moderating effect of the COVID-19 pandemic on the mental wellbeing of health care workers on sustainable employability: A scoping review - van den Broek, Anneloes; van Hoorn, Louise; Tooten, Yvette; de Vroege, Lars (Frontiers in Psychiatry, 2023)
Sustainable employability (SE) amongst healthcare workers (HCW) is an important asset for healthcare institutions. However, SE is under strain due to high work pressure, a shortage of employees, and absenteeism amongst employees based on mental problems. These developments had already started before the COVID-19 pandemic. The aim of this review is to explore whether there is a moderating effect of the COVID-19 pandemic on the mental wellbeing of HCW in the context of SE. A double blinded systematic review was conducted for this article in accordance with preferred reporting items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Eligible studies were subjected to quality evaluation and narrative synthesis. The analysis of the selected literature led to the understanding that mental problems amongst HCW were already abundantly present before the COVID-19 pandemic. Mental health problems have increased in prevalence, severity, and variation. In general, a negative relation between (mental) health and SE exists. Our findings show that mental health problems have heavily impacted the SE of HCW: absenteeism has increased and perspective on work has changed. It is time to prioritize the mental health of HCW to prevent acute care capacity from declining even further and ending up in a vicious circle.